Calculation Method for Settlement Deformation of Existing Tunnel Induced by Underpass Construction - Lan Cao; Jie Zhang; Jia-Hua Xie; Yu-Liang Lin; Guo-Lin Yang (Applied Sciences)
To explore the calculation method of settlement and deformation of existing tunnels induced by excavation, the energy method is adopted to analyze the work done by the existing tunnels with additional loads during excavation and the additional stresses caused by shield cutter thrust, shield shell, etc. The study integrates Mindlin’s stress solution and three-dimensional Loganathan’s formula to determine the friction, grouting pressure, and stratum loss. The primary objective of this approach is to identify the settlement and deformation of the existing tunnel. It is envisaged that the deformation of tunnels can be resolved by minimizing the total potential energy of the system. Relying on a new construction project, part of the Macao Sewerage Pipeline, the reasonableness and accuracy of theoretical model are verified by comparing it with the results of on-site monitoring and numerical analysis. Meanwhile, parameter sensitivity analysis is carried out to determine the sensitivity factors, including tunnel depth, diameter, and ground loss rate, on the settlement of existing tunnel, and suggestions for optimization on project are provided. The findings demonstrate the efficacy of the theoretical method in predicting the settlement and deformation of existing tunnels. Furthermore, it is evident that it can mitigate the settlement of existing tunnels by increasing the depth of new tunnels. Additionally, expanding the diameter of excavation is also a significant factor. Conversely, an increase in excavation rate will lead to an enhancement in the loss of ground layer, thereby augmenting the settlement of existing tunnels. It is noteworthy that the diameter of excavation exerts the most substantial influence on the settlement, followed by the rate of loss of ground layer, and to a lesser extent, the depth of the buried tunnel.